Channel Structures of Online Retail Platforms - Ha, Albert Y.; Tong, Shilu; Wang, Yunjie (Manufacturing and Service Operations Management, 2022)
Problem definition: This paper investigates the channel choice problem of an online platform that exerts service effort to enhance the demand in its sales channels. Academic/practical relevance: In the existing literature on the channel structure of an online retail platform, it is usually assumed that a manufacturer sells through either the platform’s agency or reselling channel but not both. In practice, many manufacturers sell the same products through both channels of the same online retail platform, a phenomenon that cannot be explained by the existing theory. Moreover, online retail platforms routinely invest in retail services that enhance the demand in their sales channels. Methodology: We develop a game-theoretic model to investigate the equilibrium channel choice, wholesale price, and retail quantity decisions. We also conduct sensitivity analysis to evaluate the impact of some parameters on the equilibrium. Results: We derive conditions under which each of the three channel structures (agency channel, reselling channel, and dual channel) emerges in equilibrium. We show that the wholesale price in the reselling channel is reduced because of the addition of the agency channel even when both channels are equally efficient, which extends the wholesale price effect because of the addition of a less efficient direct channel in the supplier encroachment literature. Our analysis highlights the flexibility of a dual channel for firms to shift sales between the two channels, which could increase the retail platform’s incentive to exert service effort. Managerial implications: Our study provides useful insights to managers to understand and make channel choice decisions in supply chains with manufacturers selling through online retail platforms.